Evaluation of Clinical Nursing Practice Programme with Preceptorship Supervision (Stake’s Countenance Evaluation Model) - Syamsul Anwar; Yetti Supriyati; Burhanuddin Tola (Jurnal Ners, 2019)
Introduction: Preceptorship is clinical education for nursing students by conducting constructive partnerships between nurse educators and practitioners. Therefore, the purpose of this study was to find out the effectiveness of the preceptorship programme using the Stake Model Evaluation Programme in terms of aspects antecedents, transactions, outcomes and behaviours.Methods: This study uses descriptive design with quantitative and qualitative approaches. The sample consists of 131 students, 22 clinical preceptors and 22 academic preceptors. The quantitative data were collected using questionnaires, observation and document studies. Qualitative study was conducted using an interview. Descriptive analysis uses mean, standard deviation, percentage, frequency distribution and qualitative analysis using a content analysis.Results: The study evaluation found that at antecedent stage. About 68.2% to 90.9% clinical preceptors had a good preparation on the student preparation stages as perceived by the academic preceptor and preceptee. While in the stage of transaction, preceptors are able to teach nursing care and students to perform nursing care from simple to complex in accordance with the competencies achieved.  Only less than half (45.5%) of students had good implementation of nursing care, including assessment, diagnosis, planning, implementation and evaluation.  However, more than 68% of them showed good professional attitudes and communication. The outcome phase obtained consistency in the result of the practice phase with the national competency test with value from 76.2% to 97.4%.Conclusion: The majority of the antecedent, transaction stage, and outcome showed an average condition which requires an improvement in order to provide a good quality education programme. Future studies may also need to design an alternative approach for students’ supervision in clinic.